직장인의 창업생태계 인식이 창업의도에 미치는 영향에 관한 실증연구: 창업자기효능감의 매개효과 중심으로 - 정행로(Haengro Jung); 양동우(Dongwoo Yang) (대한경영학회지, 2021)
펜데믹 상황에서 전 세계적으로 지속되는 경제 불황, 고용 침체, 사회 혼란 등으로 주요 선진국과 많은국가에서 기업가정신 고취와 창의적인 인재 육성을 국가 차원의 최우선 전략 과제로 제시하며 기업가정신생태계 활성화를 위한 다각적인 노력을 기울이고 있다. 따라서 본 연구의 목적은 직장인이 창업하고자 하는데 있어서 창업생태계(Entrepreneurial Ecosystem) 환경에 대한 인식이 창업의도에 어떠한 영향을 미치는지, 그리고 창업생태계 인식이 창업자기효능감를 통하여창업의도에 미치는 영향을 실증분석하였다. GEM의 프레임워크를 바탕으로 기업가적 생태계의 9가지 주요지표 중 재무적환경, 정부정책, 창업교육, 시장개방성, 문화사회규범 등 5개 분야를 선정하였다. 초기 창업을하고자하는 예비창업자에게는 금융에 대한 접근뿐만 아니라 정부 지원 및 정책, 시장 환경 등의 창업생태계가창업 성공을 위한 핵심요소이며, 문화사회적으로 기업가에 대한 인식도 중요한 요인으로 작용한다. 본 연구 결과는 창업생태계에 대한 직장인들의 인식이 창업자기효능감을 통해 창업의도에 직간접적으로영향을 미친다는 것을 보여준다. 첫째로 창업생태계 요인 중에서 시장개방성과 문화사회적규범에 대한 인식이창업의도에 유의한 영향을 주었다. 둘째로 창업생태계 하위 요인들에 대한 인식과 창업자기효능감과 창업의도간의 관계에서 시장개방성 인식이 창업자기효능감에 유의한 영향을 미쳤으며, 창업자기효능감이 창업의도에영향을 미쳤다. 셋째로 창업자기효능감은 시장개방성 인식과 창업의도 간에 관계에서 완전매개효과가 있었다. 이러한 결과는 정부나 지자체 등 정책 입안자들이 직장인의 창업자기효능감과 기업가가 되려는 의도를지원하고 강화하는 적절한 제도적 인프라, 지원구조 및 문화를 갖춘 창업생태계 구축에 초점을 맞춰야한다는것을 시사한다. 더욱이 본격적인 4차 산업혁명으로 인한 사회구조와 펜데믹으로 인한 산업생태계 변화가 급변하고 있다. 이러한 상황에서 창업자기효능감의 매개효과는 시장개방성(시장역동성)이 창업자기효능감을 통해창업의도에 미치는 중요한 요소임을 시사한다. Amid the Pendemic situation, major advanced countries and many countries are making various efforts to revitalize the entrepreneurship ecosystem by presenting entrepreneurship promotion and creative talent as top strategic tasks. Consequently, the objective of this study was to demonstrate how an employee’s perception of the entrepreneurial ecosystem environment affects entrepreneurial intention and the effect of entrepreneurial ecosystem recognition on entrepreneurial intention through entrepreneurial self-efficacy. Based on GEM’s framework, five areas such as financial environment, government policy, start-up education, market openness and cultural and social norms were selected out of total of nine major metrics of the entrepreneurial ecosystem. For prospective entrepreneurs who want to start an early business, not only access to finance, but also entrepreneurial ecosystems such as government support, policy, and market environment are key factors for success in start-ups, and awareness of entrepreneurs in culture and society is also an important society. The results of this study show that workers’ perception of the entrepreneurial ecosystem directly or indirectly affects entrepreneurship through entrepreneurial self-efficacy. Many prior studies have shown that entrepreneurial ecosystem factors are set as a variable, and the resulting analysis shows that entrepreneurial ecosystem factors increase entrepreneurial self-efficacy and also have a positive impact on entrepreneurial intentions. However, in this study, empirical analysis of entrepreneurial ecosystem factors extended to subconcepts demonstrated different effects. First, among the factors of the entrepreneurial ecosystem, market openness and awareness of cultural and social norms have had a significant impact on the intention of entrepreneurship. Second, recognition of entrepreneurial ecosystem subfactors and market openness recognition in the relationship between entrepreneurial self-efficacy and entrepreneurial intent had a significant impact on entrepreneurial self-efficacy. Third, the sense of entrepreneurial self-efficacy had a full mediation effect effect on the relationship between market openness recognition and entrepreneurial intentions. Unlike many prior studies on university students, these results are presumed to be due to the nature of research on office workers. That is, it is estimated that employees have already experienced and observed corporate management directly or indirectly at the working level, so they are not significantly affected by the perception of the financial environment, government and local governments’ policies or support programs, or entrepreneurial education. On the other hand, the rapidly changing market conditions (market dynamics) in the fourth industry and pendemic situation, which have begun in earnest, are seen as a key factor in considering the intention of starting a business. Furthermore, the fear of failure to start a new business seems to play a major role in encouraging risk taking, respect for entrepreneurs who succeed in start-ups, and cultural and social norms that encourage and actively support start-ups. These results also suggest that policymakers, such as governments and local governments, should focus on building an entrepreneurial ecosystem with appropriate institutional infrastructure, support structures and cultures that support and strengthen the worker’s entrepreneurial self-efficacy and intention to become entrepreneurs. Moreover, changes in the social structure and industrial ecosystem caused by the fourth industrial revolution are rapidly changing. In this situation, the medium effect of entrepreneurial self-efficacy suggests that market openness (market dynamics) is an important factor in entrepreneurial intentions through entrepreneurial self-efficacy. KCI Citation Count: 0